KONDISI TERUMBU KARANG PULAU MANTEHAGE KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Ardy Kase; Indri manembu; Joshian Schaduw (JURNAL PESISIR DAN LAUT TROPIS, 2019)
Coral reefs are coastal ecosystems with the highest level of diversity. Corals are invertebrates that are included in the Phylum Coelenterata (hollow animal) or Cnidaria. Whereas coral reefs are a collection of millions of polyps. Natural phenomena and various anthropogenic activities threaten the health and presence of Mantehage Island coral reefs and the lack of information about the health conditions of coral reefs on Mantehage Island. The purpose of this study is to determine the condition of coral reefs andto Â provide baselines data on Mantehage Island. Data collection was done by using UPT Â method (Underwater Photo Transect). Underwater Photo Transect carried out by underwater shooting using a digital camera that was shielded (housing). Image analysis were done using the CPCe software (Coral Point Count with Excel extensions). The results of coral reef health conditions at four stations on Mantehage Island shows, coral reef cover at each station as follows, station 1 (one) 53.00% were in good condition, station 2 (two) 25.40% were in a moderate condition, station 3 (three) 16.49% were in poor condition, and station 4 (four) 42.07% were in a moderate condition. From the four stations, the condition of Mantehage Island's coral reefs were in the moderate category with a percentage of 34.24%.Keywords:. Mantehage Island, Terumbu Karang, UPT, CPCe